Vital protocols for PolyWare™ measurement reliability and accuracy - Min Lee, Jong; Baek, Seung-Hoon; Soo Lee, Yeon (Frontiers in Surgery, 2022)
Background and Objective: PolyWareTM software (PW) has been an exclusively used software in most polyethylene wear studies of total hip arthroplasty (THA). PW measurements can be significantly inaccurate and unrepeatable depending on imaging conditions or subjective manipulation choices. In this regard, this study aims to reveal the required conditions to achieve the best accuracy and reliability of the PW measurements. Methods: The experiment examined the dependency of PW on several measurement conditions. The X-ray images of in-vitro THA prostheses were acquired under a clinical X-ray scanning condition. A combination of the liner wear of 6.67 mm, the acetabular lateral inclination of 36.6°, and the anteversion of 9.0° was simulated. Results: Among all the imported X-ray images, those with a resolution of 1076×1076 exhibited the best standard deviation in wear measurements as small as 0.01 mm and the least occurrences of blurriness. The edge detection area specified as non-squared and off the femoral head center exhibited the most happening of blurriness. The X-ray image that scans a femoral head eccentrically placed by 15 cm superior to the X-ray beam center led to a maximum acetabular anteversion measurement error of 5.3°. Conclusion: Because PW has been an exclusively used polyethylene wear measurement tool, revealing its error sources and making the countermeasure are of great importance. The results request PW users to observe the following measurement protocols; 1) the original X-ray image be 1076×1076 squared X-ray images, 2) the edge detection area be specified as a square with edge lengths of 5 times the diameter of the femoral head centered at the femoral head center, 3) the femoral head center or acetabular center be placed as close to the center line of the X-ray beam as possible, at the X-ray scanning moment.